Regional differences in land use affect population performance of the threatened insectivorous plant Drosophyllum lusitanicum (Droseraceae) (Diversity and Distributions, 2003)
We analyse populations of the insectivorous plant Drosophyllum lusitanicum (L.) Link (Droseraceae) and their habitats throughout the species’ distribution range (Portugal, Spain and Morocco), and examine their relations. We have surveyed 32 populations and we analyse their demographic structures, accompanying plant communities (by TWINSPAN analyses), and relationships between population features and several edaphic and nonedaphic environmental variables (by multiple regression analyses). Plant communities, their ﬂoristic richness and degree of endemism change across the geographical range of Drosophyllum. Populations vary strongly in size, density and age structure. Their recruitment seems largely determined by competition with the surrounding vegetation, while only weak relationships were detected between population performance and other environmental factors. The demographic structure of populations exhibits a marked geographical differentiation, with populations becoming older and sparser towards the north-western part of the range. The largest and presumably most stable populations are mostly found in southern Spanish heathlands, which are nowadays scarcely affected by man. Moroccan populations suffer from browsing by cattle and experience an accelerated generation turnover, while most Portuguese populations occur in afforested areas and experience strongly reduced recruitment. The historical distribution range of Drosophyllum within its peculiar habitat has probably been relatively stable, but recent regional differences in human land use have resulted in present-day differences in population performance, as well as in types and degrees of threat across the three countries involved. Conservation strategies should take into account this range-wide variation and combine approaches on different spatial scales.